Abdominal wall hematoma as a complication of drainage after laparoscopic cholecystectomy: a case report - Juntao Li; Zixiong Liu; Jia Li; Wei Cheng (Frontiers in Medicine)
BackgroundAbdominal wall hematoma represents a potential postoperative complication that requires prompt identification and appropriate management. This case report retrospectively analyzes a patient who developed an abdominal wall hematoma associated with a drainage tube and puncture site following laparoscopic cholecystectomy at our hospital. The clinical characteristics, treatment modalities, and relevant literature are reviewed to highlight strategies for the prevention and management of postoperative hematomas, with the aim of providing valuable insights for clinical practice. We managed a patient who had undergone laparoscopic cholecystectomy for gallstones complicated by cholecystitis. On the first postoperative day, a hematoma developed at the site of the abdominal drainage tube insertion. Despite initial attempts at hemostasis through abdominal wall compression, these measures proved ineffective, necessitating the use of a urinary catheter balloon for effective compression hemostasis.Case presentationWe treated a patient who had undergone laparoscopic cholecystectomy for gallstones complicated by cholecystitis. On the first postoperative day, a hematoma developed at the site of the abdominal drainage tube insertion. Despite initial attempts at hemostasis using abdominal wall compression, these measures were ineffective, necessitating the use of a urinary catheter balloon for effective compression hemostasis.ConclusionThe urinary catheter balloon tamponade was effectively employed postoperatively to achieve hemostasis for the hematoma at the abdominal wall drainage site. It provides a viable alternative for early intervention in hematoma management.